TRANSLATION AND CROSS LANGUAGE VALIDATION OF SUBJECTIVE HAPPINESS SCALE IN URDU LANGUAGE - Dr. Anila Sadaf Mubashir; Ms. Rida Kainaat; Ms. Qurat.ul.Ain; Dr. Maria Anwar; Ms. Ambar Muzzammil (International Journal of Contemporary Issues in Social Sciences, 2024)
This paper explores the concept of subjective happiness within the framework of positive psychology. It discusses how subjective happiness, comprising joy, contentment, and overall well-being, influences various aspects of human experience. Drawing on seminal works by Lyubomirsky and Diener, it highlights subjective happiness as a multifaceted construct with affective and cognitive components. The significance of subjective well-being, encompassing positive affect, negative affect, and life satisfaction, is also examined. The paper reviews the psychometric properties and cross-cultural validity of the Subjective Happiness Scale (SHS), emphasizing its relevance across diverse populations, including Urdu-speaking Pakistanis. Additionally, it explores the practical implications of subjective happiness on work performance, social interactions, and overall well-being. Lastly, it discusses the growing emphasis on subjective happiness in global well-being initiatives. Overall, this paper aims to deepen our understanding of human well-being and inform future research and interventions aimed at promoting happiness and flourishing worldwide.